A superlattice interface and S-scheme heterojunction for ultrafast charge separation and transfer in photocatalytic H2 evolution - Sijie Wan; Wang Wang; Bei Cheng; Guoqiang Luo; Qiang Shen; Jiaguo Yu; Jianjun Zhang; Shaowen Cao; Lianmeng Zhang (Nature Communications)
Abstract The rapid recombination of photoinduced charge carriers in semiconductors fundamentally limits their application in photocatalysis. Herein, we report that a superlattice interface and S-scheme heterojunction based on Mn0.5Cd0.5S nanorods can significantly promote ultrafast charge separation and transfer. Specifically, the axially distributed zinc blende/wurtzite superlattice interfaces in Mn0.5Cd0.5S nanorods can redistribute photoinduced charge carriers more effectively when boosted by homogeneous internal electric fields and promotes bulk separation. Accordingly, S-scheme heterojunctions between the Mn0.5Cd0.5S nanorods and MnWO4 nanoparticles can further accelerate the surface separation of charge carriers via a heterogeneous internal electric field. Subsequent capture of the photoelectrons by adsorbed H2O is as fast as several picoseconds which results in a photocatalytic H2 evolution rate of 54.4 mmol·g−1·h−1 without any cocatalyst under simulated solar irradiation. The yields are increased by a factor of ~5 times relative to control samples and an apparent quantum efficiency of 63.1% at 420 nm is measured. This work provides a protocol for designing synergistic interface structure for efficient photocatalysis.